2000
DOI: 10.1080/13921657.2000.10512337
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Activity of the Roach (Rutilus RutilusL.) Intestinal Microflora

Abstract: For research, two differently polluted lakes were selected: Lake Dringis, Aukðtaitija National Park, as an ecosystem pattern of a weak anthropogenic influence, and Lake Drûkðiai, as a regularly polluted water body. Lake Drûkðiai, the cooling basin of Ignalina Nuclear Power Plant, through its tributaries is being polluted with industrial and municipal sewage. Samples were taken from four differently polluted mouths of tributaries: the mouth of the Rièanka Stream; the mouth of the Gulbinës Stream affected by urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
(5 reference statements)
1
7
0
Order By: Relevance
“…Investigation results suggest that bacteria of the genera Aeromonas, Pseudomonas and Flavobacterium-Cytophaga prevail in the bacteriocenoses of the digestive tract of freshwater fish (Ringø and Birkbeck 1999; Vesta Skrodenyte-Arbaeiauskiene 2000; Voveriene et al 2002). The impact of feeding intensity and food on the qualitative and quantitative composition of intestinal bacteriocenoses of fish was studied by a number of scientists (Ringo and Olsen 1999;Pucci et al 2004;Vesta Skrodenyte-Arbaeiauskiene 2000;Voveriene et al 2002). The structure of intestinal bacteriocenoses of fish is influenced by farming conditions of fish, too (Ringo and Strom 1994).…”
Section: Nature Of Microflora In Fish Digestive Tractmentioning
confidence: 99%
“…Investigation results suggest that bacteria of the genera Aeromonas, Pseudomonas and Flavobacterium-Cytophaga prevail in the bacteriocenoses of the digestive tract of freshwater fish (Ringø and Birkbeck 1999; Vesta Skrodenyte-Arbaeiauskiene 2000; Voveriene et al 2002). The impact of feeding intensity and food on the qualitative and quantitative composition of intestinal bacteriocenoses of fish was studied by a number of scientists (Ringo and Olsen 1999;Pucci et al 2004;Vesta Skrodenyte-Arbaeiauskiene 2000;Voveriene et al 2002). The structure of intestinal bacteriocenoses of fish is influenced by farming conditions of fish, too (Ringo and Strom 1994).…”
Section: Nature Of Microflora In Fish Digestive Tractmentioning
confidence: 99%
“…The GI microbiota of hydrobionts has been reported to contribute to the nutrition and physiological processes of the host by producing vitamins, amino acids, digestive enzymes and metabolites, similar to that of mammals (Syvokiene 1989; Cahill 1990; Sugita et al 1990; Sugita, Matsuo, Hirose, Iwato & Deguchi 1997; Mickeniene 1999; Skrodenyte‐Arbaeiauskiene 2000; Skrodenyte‐Arbaeiauskiene et al 2006). Nevertheless, a wide range of enzymes like carbohydrases, phosphatases, esterases, lipases and peptidases, cellulase, lipase and proteases (Bairagi et al 2002; Ramirez & Dixon 2003; Izvekova & Lapteva 2004) produced by GI bacteria could be a contributory source to digestive enzymes in fish.…”
Section: Role Of Gi Microbiota In Nutritionmentioning
confidence: 99%
“…; Sugita, Matsuo, Hirose, Iwato & Deguchi 1997;Mickeniene 1999;Skrodenyte- Arbaeiauskiene 2000; Skrodenyte-Arbaeiauskiene et al 2006). Nevertheless, a wide range of enzymes like carbohydrases, phosphatases, esterases, lipases and peptidases, cellulase, lipase and proteases(Bairagi et al 2002;Ramirez & Dixon 2003;Izvekova & Lapteva 2004) produced by GI bacteria could be a contributory source to digestive enzymes in ¢sh.…”
mentioning
confidence: 99%
“…are commensal a number are major pathogens of freshwater and marine fishes (Loch and Faisal 2015). It has been suggested that fish gut isolated F lavobacterium sp might be possible contributors to the digestive processes of fish by producing enzymes such as amylase (Skrodenytė-Arbačiauskienė 2000), chitinase (Ray et al 2012) and protease (Morita et al 1998; Skrodenytė-Arbačiauskienė 2000).…”
Section: Discussionmentioning
confidence: 99%